ETR300 Chak Koyy House / Glayren Anak Dennis... [et.al] - Dennis, Glayren; Tedong, Nyura; Kiai, Simon; Tony, Fefiana Lahong; Sudin, Warren Lang (2015)
The name of our company is ChakKoy House. The business has been decided in the form of five partnerships. Each partner has contributed on an agreed amount of capital as in our agreement. Our main business activity is sale cakoi cake. We are located at Kota Sentosa, 7th Miles Lorong Shiu Shan Bang 3B 93250 Kuching, Sarawak. We will be opened on 1st January 2016.